21 Analysis of the characteristics of hemorrhoids models. (19th December 2016) - Zhang, Mengfei; Miao, Mingsan; Xi, Peng; Xiang, Liling
Abstract : Objectives: Based on the characteristics of the clinical symptoms of hemorrhoids and analysis of the corresponding animal model, treatment methods are proposed. Methods: The clinical diagnosis of hemorrhoids and the therapeutic effects of Chinese medicine and Western medicine were analyzed and the establishment and characteristics of the current animal model were summarize d. The current animal model and clinical symptoms of anastomosis were analyzed and discussed in relation to clinical symptoms and standards. Results: In Western medicine, hemorrhoids are divided into external, internal and mixed hemorrhoids. There are three research models of inflamed external hemorrhoids: the croton oil and carrageenan anal edema model, the acetic acid bacteria and ulcer model, and the anal skin trauma model. The blood stasis type model is used for thrombotic external hemorrhoids. The esophageal varices model is mainly used for internal hemorrhoids. Mixed hemorrhoid models include the inferior rectal vein occlusion model and the ligation of hemorrhoids model. The above models are only approximate models of hemorrhoids as there are large differences in clinical incidence and the degree of anastomosis. More effective models of hemorrhoids must be produced, combining clinical pharmacology and related research. In addition, our laboratory has long been engaged in the study of Chinese medicine for the prevention and treatment of hemorrhoids. Research on hemorrhoid models must be strengthened in the future, and clinical close contact maintained. Conclusions: Existing animal models, in addition to the soybean oil model, are based on low quality and inadequate modeling, and are biased towards Western medicine, ignoring the combination of symptoms used in traditional Chinese medicine. The soybean oil model has good development prospects and should be improved. Acknowledgments: This research was financially supported by the National 'Eleventh Five-Year' Support Project (Grant No. 2008BAI53B09), Henan Province Outstanding Scientific and Technological Innovation Team (Grant No. TCJ2014-391) and Zhengzhou Science and Technology Innovation Team Project (Grant No. 131PCXTD612).